Hemophagocytic Lymphohistiocytosis in Pregnancy: A Case Series and Review of the Current Literature - Jessica Parrott; Alexander Shilling; Heather J. Male; Marium Holland; Cecily A. Clark-Ganheart (Hindawi Limited, 2019)
Background. Hemophagocytic lymphohistiocytosis (HLH) is a rare disease that can be fatal in pregnancy. We report two cases of severe HLH that highlight etoposide use in pregnancy. Case 1. 28-year-old G2P1 with lupus presented at 18 weeks with acute hypoxic respiratory failure, hepatic dysfunction, leukopenia, thrombocytopenia, and elevated ferritin. Bone marrow biopsy confirmed HLH. Etoposide and corticosteroid treatment was initiated per HLH protocol; however clinical status declined rapidly. Fetal demise occurred at 21 weeks and she subsequently suffered a massive cerebral vascular accident. She was transitioned to comfort measures and the patient deceased. Case 2. 37-year-old G4P3 presented at 25 weeks with fever, acute liver failure, thrombocytopenia, and elevated ferritin. HLH treatment was initiated, including etoposide, and diagnosis confirmed with liver biopsy. Fetal growth restriction was diagnosed at 27 weeks. Delivery occurred at 37 weeks. The neonate was found to be CMV positive despite negative maternal serology. Conclusion. The addition of etoposide to corticosteroid use is a key component in HLH treatment of nonpregnant individuals. While this is usually avoided in pregnancy, the benefit to the mother may outweigh the potential harm to the fetus in severe cases and it should be strongly considered.